KEANEKARAGAMAN JENIS KEPITING BIOLA (Uca spp.) DI HUTAN MANGROVE â€œMEMPAWAH MANGROVE PARKâ€ DESA PASIR KECAMATAN MEMPAWAH HILIR KABUPATEN MEMPAWAH - Sari, Indah Permata; Prayogo, Harri; Burhanuddin, . (Universitas Tanjungpura, 2018)
AbstractFiddler crab (Uca spp.) is a unique type of small Uca crab that lives in a detritus-eating mangrove ecosystem. This kind of crab has a very important role, namely keystone species. Fiddler crab is included in the decapoda order, which is a group of Ocypodidae invertebrate families. The purpose of this study was to examine the diversity of fiddler crab species (Uca spp.). Based on habitat types and the benefits of research as a keystone species of mangrove ecosystem as a basis for efforts in preserving fiddler crab (Uca spp.). This research is a quantitative descriptive study with a survey and direct site-observation as the techniques of collecting data (Suprayogi et al., 2014). Line placement is done by purposive sampling which divided the area over three lines according to conditions of the field. Namely, line 1 was placed in front of the coastal area near the sea, line 2 was placed in the middle of which was overgrown with mangroves. Meanwhile, line 3 was placed behind the area that was more inland. The path length is 100 meters, which consists of 33 plots placed on the right and left side of the transect line with a distance between the plots of 2 m. The results of the study found 8 types of fiddler crabs, namely Uca paradussumieri, Uca dussumieri, Uca rosea, Uca forcipata, Uca crassipes, Uca tetragonon, Uca acuta and Uca annulipes with 333 individuals. Specifically, for fiddler crab of Uca annulipes type, there were 6 varieties based on the color and shape of the carapaceand the shape of the claws. The species diversity index Â in the three research lines was classified as low because it ranged from 0,49 to 0,79. The physical-chemical factors of the environment in the three pathways were the pH of weak-alkali substrates ranging from 27-28 degrees Celsius, and low-salinity which was still in accordance with Ucaâ€™s life, that is 20.00 ppt. The soil texture consisted of three lines categories, line 1 which comprised lane 1.1 for clay-dusty land texture and lane 1.2 for clay-sandy texture. While line 2 was for dusty land texture, and lane 3 was for clay-dusty land texture. Keywords: Biodiversity, Fiddler Crab, Mangrove forest, Uca